Bioetika, sport a geneticky zvýhodnený atlét - Miah, A. (Medicinska Etika & Bioetika, 2002)
This paper begins by acknowledging the interest taken by various international organisations in genetic enhancement and sport, including the US President`s Council on Bioethics (July, 2002) and the World Anti-Doping Agency (March, 2002). It is noticed how sporting organisations have been particularly concerned to emphasise the `threat` of genetics to sport, whereas other institutions have recognised the broader bioethical issues arising from this prospect, which do not readily reject the use of genetic technology in sport. Sports are identified as necessarily `human` and `moral` practices, the exploration of which can reveal greater insight into the intuitive fears about genetic modification. It is argued that anti-doping testing measures and sanctions unacceptably persecute the athlete. While there are substantial reasons to be concerned about the use of genetic modification in sport, the desire for policy ought not diminish the need for ethical research; nor ought such research embody the similar guise of traditional `anti` doping strategies. Rather, the approach to genetics in sport must be informed more by broader social policies in bioethics and recognition of the greater goods arising from genetic technology.